2019
DOI: 10.1161/hypertensionaha.118.12137
|View full text |Cite
|
Sign up to set email alerts
|

Role of Corin in Blood Pressure Regulation in Normotensive and Hypertensive Pregnancy

Abstract: Corin (an atrial natriuretic peptide converting enzyme) represents a potential biomarker for gestational hypertensive disorders; yet, its role in blood pressure regulation throughout pregnancy remains unclear. We investigated the time-course of change in blood corin content in relation to blood pressure and sympathetic nerve activity throughout pregnancy. Forty-four women (29±0.9 yrs) participated. Following-term, 23 had 'low-risk' (no personal history of gestational hypertensive disorders) normal pregnancies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 48 publications
1
42
0
1
Order By: Relevance
“…Indeed, our recent longitudinal study showed that women who developed gestational hypertension had similar height but much greater body weight compared with women who had normotensive pregnancies (e.g., the mean difference in body weight between the groups prior to and during pregnancy was about 28 kg). 97 Furthermore, throughout early and late pregnancy, as well as postpartum, resting MSNA was significantly greater in women with gestational hypertension than in women with normotensive pregnancies (Fig. 6).…”
Section: Obesity Sympathetic Activity and Gestational Hypertensionmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, our recent longitudinal study showed that women who developed gestational hypertension had similar height but much greater body weight compared with women who had normotensive pregnancies (e.g., the mean difference in body weight between the groups prior to and during pregnancy was about 28 kg). 97 Furthermore, throughout early and late pregnancy, as well as postpartum, resting MSNA was significantly greater in women with gestational hypertension than in women with normotensive pregnancies (Fig. 6).…”
Section: Obesity Sympathetic Activity and Gestational Hypertensionmentioning
confidence: 87%
“…6). 97 Studies from our laboratory and others have suggested that normal pregnancy is associated with sympathetic activation that occurs in the first trimester, sustains throughout the entire course of gestation, and returns to the prepregnancy level after delivery [97][98][99][100][101][102][103] while sympathetic overactivity may lead to the development of gestational hypertensive disorders. 97,100,104…”
Section: Obesity Sympathetic Activity and Gestational Hypertensionmentioning
confidence: 98%
“…The mechanism(s) responsible for this increased risk are likely multifaceted but may in part be due to altered withinpregnancy sympathetic neural regulation in women with multiple pregnancies. Certainly, sympathetic nerve activity (SNA) is augmented (in the range of 50 to 150%) throughout normal pregnancy, occurring as early as 6 wk gestation and peaking within the second or third trimester, as a means to ensure adequate cardiovascular homeostasis (1,6,7,10,15). Yet, when such activation occurs in excess, hypertensive disorders of pregnancy likely manifest, i.e., gestational hypertension and/or preeclampsia (1,2,13).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, sympathetic nerve activity (SNA) is augmented (in the range of 50 to 150%) throughout normal pregnancy, occurring as early as 6 wk gestation and peaking within the second or third trimester, as a means to ensure adequate cardiovascular homeostasis (1,6,7,10,15). Yet, when such activation occurs in excess, hypertensive disorders of pregnancy likely manifest, i.e., gestational hypertension and/or preeclampsia (1,2,13). Similarly, sympathetic overactivity is associated with cardiovascular pathology in nonpregnant populations, including hypertension, coronary artery disease, heart failure, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, corin deficiency abolishes ANP activation (25,26). Both corin and ANP are expressed in the pregnant uterus (27)(28)(29)(30)(31). In mice, corin or ANP deficiency impairs trophoblast invasion and spiral artery remodeling, leading to a preeclampsialike phenotype (27,28,32).…”
Section: Introductionmentioning
confidence: 99%